PERAMALAN ESTIMATED ULTIMATE RECOVERY MENGGUNAKAN METODE WATER OIL RATIO PADA SUMUR X - Dorothea Dyah Puspita; Onnie Ridaliani; Listiana Satiawati (Journal of Mechanical Engineering and Mechatronics, 2018)
In the management of oil and gas fields, production forecasting is needed to find out the steps to be taken in the future. Therefore, in this study the prediction of the well potential was carried out using the water oil ratio method. The prediction of potential wells referred to in this study is to predict the estimated ultimate recovery (EUR) or cumulative value of oil production in the future. Well X has a well problem in the form of excess water production and after being analyzed using Chan’s Diagnostic Plot, the result is that the well has water channeling. The type of water channeling is in well X experiencing near wellbore channeling. After knowing the type of water problem, a prediction of the potential of the well (cumulative maximum production) is carried out, both wells have water channeling and wells that are normal or not experiencing problems. Prediction of well potential in the form of cumulative maximum production value or Estimated Ultimate Recovery (EUR) is obtained by the water oil ratio method. This method is using five plots including water cut, oil fraction, cumulative WOR, cumulative watercut, and finally 1 / fw which is compared with each with maximum cumulative production. Then after it was discovered that the EUR value of each well experienced both water and normal problems, it was found to lose the cumulative prediction of the production of each well. The loss of EUR well X is 551,267 STB.